2014
DOI: 10.3390/nu6020517
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity of Red Ginseng against Influenza A Virus Infection

Abstract: Ginseng herbal medicine has been known to have beneficial effects on improving human health. We investigated whether red ginseng extract (RGE) has preventive effects on influenza A virus infection in vivo and in vitro. RGE was found to improve survival of human lung epithelial cells upon influenza virus infection. Also, RGE treatment reduced the expression of pro-inflammatory genes (IL-6, IL-8) probably in part through interference with the formation of reactive oxygen species by influenza A virus infection. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…3B). These results were consistent with previous reports that the ginsenosides of Radix Ginseng Rubra [8] and phenylethanoid glycosides of Radix Rehmanniae Praeparata [10] played important roles in improving immunity. In addition, echinacoside of fraction 3 also exhibited positive effect on bone marrow cells.…”
Section: Immune-enhancement Effect On Bone Marrow Cellssupporting
confidence: 95%
See 1 more Smart Citation
“…3B). These results were consistent with previous reports that the ginsenosides of Radix Ginseng Rubra [8] and phenylethanoid glycosides of Radix Rehmanniae Praeparata [10] played important roles in improving immunity. In addition, echinacoside of fraction 3 also exhibited positive effect on bone marrow cells.…”
Section: Immune-enhancement Effect On Bone Marrow Cellssupporting
confidence: 95%
“…The peptides of Colla corii asini could promote hematopoiesis by activating immature granulocyte and erythroid cells [6]. Radix Ginseng Rubra and Codonopsis pilosula had anti-oxidative [7] and immune-modulatory activity [8]. Radix Ginseng Rubra also demonstrated anti-bacterial, anti-obesity and anti-diabetic activities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Following infection, the process of influenza replication can induce intracellular ROS in host cells [57,58], which could contribute to oxidative damage to the host genome. Indeed, ectopic expression of influenza matrix (M2) protein alone in human lung epithelial cell lines (A549 and H441) is sufficient to elevate intracellular and mitochondrial reactive oxygen species [51].…”
Section: Discussionmentioning
confidence: 99%
“…Many independent reports have suggested that agents capable of interfering with the influenza‐initiated host–pathogen signalling pathways and/or possessing direct antiviral effect, either as inherent properties of a single agent or as a combination therapy could be useful in this regard . Lately, an aggressive interest has been on evaluating and validating immunomodulators for their alternative, adjuvant or adjunctive anti‐influenza roles . Here, we have evaluated the immunomodulatory effect of kolaviron, a natural antioxidant and anti‐inflammatory agent, on the expression of specific moderators of immune‐mediated pathology in BALB/c mice challenged with influenza A/Perth/H3N2/16/09 virus (Pr/H3N2).…”
Section: Discussionmentioning
confidence: 99%